Determinants of Regional Economic Growth in Twenty Provinces in Indonesia Using a Data Panel Approach - A.Nur Fitrianti; Retno Fitrianti; Andryirawan Yakub; Andi Sopian; Hamka, Hamka; A.Baso Aditya Sapanang (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Western and Central Indonesia Regions are far superior when compared to the Eastern Indonesia Region. This is a result of a number of factors, including variations in development spending, the quantity of balancing funds, population, level of investment in the area, and the region's natural resources. The purpose of this study is to investigate and evaluate the effects of macroeconomic factors, the status of oil-rich regions, and regional government spending on regional economic growth. This analysis employs a static panel and dynamic panel approach (VECM panel). The research uses data from 20 provinces in Indonesia between 2008 and 2018, which includes complete data from 34 provinces. The study's findings demonstrate that long-term (VECM panel) spending on education, agriculture, general allocation funds, population, and foreign investment has a positive impact on regional economic growth, while spending on health, fisheries, and maritime has a negative impact. According to studies conducted using a static panel, foreign direct investment and spending on foreign direct investment, education, agriculture, fisheries, and maritime affairs have a positive impact on regional economic growth, while the General Allocation Fund has a negative impact. Research has demonstrated that the dummy variable representing regional status has a positive impact on regional economic growth. The government ensures that the state budget is allocated more optimally to overcome this problem inequality in obtaining opportunities in the education and health sectors through improvement public infrastructure services.